Myoclonus-Dystonia Syndrome and E-Sarcoglycan Deficiency - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2002)
Clinical and genetic findings in 9 European families with myoclonus-dystonia syndrome (MDS) are reported from Ludwig-Maximilians-Universitat, Munich, Germany.